Oral suction capacity in breastfeeding vs. bottle feeding. A systematic review - Guzmán Sánchez, Pilar Andrea; Arciniegas Morera, María Margarita; Cárdenas Jaramillo, Laura; Larrahondo Gómez, Mariana; Lambis Cano, Cyntia Paola; Meneses-Urrea, Luz Adriana (Frontiers in Pediatrics, 2025)
ObjectivesThis study aims to ascertain whether breastfed infants exhibit superior oral sucking abilities compared with bottle-fed infants.MethodsA systematic review was conducted, encompassing four databases associated with professional health practices: Web of Science, Scopus, PubMed, and Dimensions. The review encompassed articles published from 2010 onward, and included children up to the age of 2 y under normotypic conditions. The search was conducted using a query constructed from keywords that considered MeSH terms, and the query was applied in all databases. The systematic review was performed following PRISMA 2020 guidelines, and the methodological quality was assessed using the MINORS scale.ResultsBehaviors related to maternal suckling, such as position, mother-child bonding, adequacy of suckling, baby responses, and anatomy, showed that the group of bottle-fed babies performed poorly in the five behaviors analyzed (P < 0.001), with suckling behavior standing out.ConclusionThe mechanics of sucking exhibits differences in oral motor behavior between bottle-fed and breastfed infants, favoring the latter group. However, these disparities appear inconsequential in children receiving mixed feeding.